3) 3х – х*(15+ х) > -(х решите неравенства ​

artyom11111112 artyom11111112    1   15.02.2021 08:27    0

Ответы
Aslan006 Aslan006  17.03.2021 08:29

1) -3 * (х - 4) = 5х - 12;

-3х + 12 = 5х - 12;

-3х - 5х = -12 - 12;

-8х = -24;

х = 24 / 8 = 3;

2) (16 - 5х) - (3 - 5х) = 6;

16 - 5х - 3 +5х = 6;

13 - 0х = 6;                                                                                                        3) 26 - 4х = 3х - 7 * (х - 3);

26 - 4х = 3х - 7х + 21;                                                                                          4) -2 * (3 - 4х) + 5 * (2 - 1 , 6х) = 4;

-6 + 8х + 10 - 8х = 4;

-6 + 8х + 10 - 8х - 4 = 0;

-4х + 4х = 21 - 26;                                                                                                                                                                          

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика